Hemodynamic characteristics of stable and unstable vertebrobasilar dolichoectatic and fusiform aneurysms. (16th March 2018) - Brinjikji, Waleed; Chung, Bongjae; Yong-Hong, Ding; Wald, John T; Mut, Fernando; Kadirvel, Ramanathan; Kallmes, David F; Rouchaud, Aymeric; Lanzino, Giuseppe; Cebral, Juan R
Abstract : Background and purpose: Vertebrobasilar dolichoectatic and fusiform aneurysms (VBDAs) are known to have a poor natural history, with high rates of growth, rupture, and stroke. The purpose of this study was to identify hemodynamic characteristics that differ between VBDAs associated with growth, rupture, and stroke. Materials and methods: VBDAs with CT angiography or MR angiography followed longitudinally without treatment were studied. Unstable aneurysms were defined as those that grew or ruptured during follow-up. Aneurysms associated with stroke were defined as those associated with posterior circulation infarct at follow-up. Baseline data, including demographics, comorbidities, and aneurysm morphology and size were collected. Image based computational fluid dynamics models were created and run under pulsatile flow conditions. Relevant hemodynamic and geometric variables were calculated and compared between groups (stable vs unstable and no stroke vs stroke) using the Wilcoxon test. Results: A total of 37 VBDAs were included (24 stable, 13 unstable; 30 no stroke, 7 stroke). Unstable aneurysms had lower shear rates (P=0.05), blood flow velocity (P=0.03), and lower vorticity (P=0.049) than stable aneurysms. In addition, unstable aneurysms had higher mean oscillatory shear indices (P=0.001). There were no differences in the hemodynamic characteristics of aneurysms in the stroke group compared with the non-stroke group. Conclusion: This small study suggests there may be hemodynamic differences between unstable and stable VBDAs. Unstable VBDAs appear to be under lower flow conditions with lower velocity, vorticity, and shear rates, and have more oscillatory flow. There was no difference in the hemodynamic characteristics of aneurysms in the stroke and no stroke group.